A contingent assessment of the structural and governance characteristics of interconnected dyads in multitier supply chains. Issue 5 (3rd June 2019) - Mahapatra, Santosh K.; Narasimhan, Ram; Barbieri, Paolo
Abstract : Purpose: The purpose of this paper is to examine the buyer–supplier exchange dynamic in terms of the influence of product and market contingencies on the interfirm connectivity, governance and exchange performance of interconnected dyads in multitier supply chains (MSCs). Design/methodology/approach: Using an inductive approach, the authors analyzed the supply network of a high-end motorcycle manufacturer (OEM). Four sets of "interconnected dyads" constituting four embedded units of analysis were considered, each involving the OEM, its tier 1 and corresponding tier 2 suppliers. These interconnected dyads representing four strategic components and their sub-components offer contrasts in terms of product and market contingencies. Findings: This analysis reveals that product and market contingencies influence patterns of dependence among firms. These in turn impact interfirm connectivity (i.e. structural characteristic), and the degree of contract formalization, collaboration and concentration of decision-making power (i.e. governance characteristics) in the interconnected dyads. The authors also found that structural and governance aspects can have mutual influence, leading to satisfactory or unsatisfactory outcomes. Propositions synthesizing the relationships among the constructs are developed. Research limitations/implications: The constructs and their underlying relationships need to be further refined if we are to devise hypotheses and validate them at a large-scale empirical level. Originality/value: This is one of the first studies to explore the influence of business contingencies on the complex buyer–supplier exchange dynamic in MSCs having a "beyond the dyad" perspective. The authors address why and how various types of interconnectivity are developed, and how the interplay among interfirm dependence, connectivity and governance influences the suppliers' performance in the MSCs.